-.166(x-18)+0.333(x+3)=x-11

Simple and best practice solution for -.166(x-18)+0.333(x+3)=x-11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -.166(x-18)+0.333(x+3)=x-11 equation:


Simplifying
-0.166(x + -18) + 0.333(x + 3) = x + -11

Reorder the terms:
-0.166(-18 + x) + 0.333(x + 3) = x + -11
(-18 * -0.166 + x * -0.166) + 0.333(x + 3) = x + -11
(2.988 + -0.166x) + 0.333(x + 3) = x + -11

Reorder the terms:
2.988 + -0.166x + 0.333(3 + x) = x + -11
2.988 + -0.166x + (3 * 0.333 + x * 0.333) = x + -11
2.988 + -0.166x + (0.999 + 0.333x) = x + -11

Reorder the terms:
2.988 + 0.999 + -0.166x + 0.333x = x + -11

Combine like terms: 2.988 + 0.999 = 3.987
3.987 + -0.166x + 0.333x = x + -11

Combine like terms: -0.166x + 0.333x = 0.167x
3.987 + 0.167x = x + -11

Reorder the terms:
3.987 + 0.167x = -11 + x

Solving
3.987 + 0.167x = -11 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
3.987 + 0.167x + -1x = -11 + x + -1x

Combine like terms: 0.167x + -1x = -0.833x
3.987 + -0.833x = -11 + x + -1x

Combine like terms: x + -1x = 0
3.987 + -0.833x = -11 + 0
3.987 + -0.833x = -11

Add '-3.987' to each side of the equation.
3.987 + -3.987 + -0.833x = -11 + -3.987

Combine like terms: 3.987 + -3.987 = 0.000
0.000 + -0.833x = -11 + -3.987
-0.833x = -11 + -3.987

Combine like terms: -11 + -3.987 = -14.987
-0.833x = -14.987

Divide each side by '-0.833'.
x = 17.99159664

Simplifying
x = 17.99159664

See similar equations:

| 15(-42x+40)=15(-8+2440) | | 6t^2-84t+240= | | 8-16x=40 | | w^2-15w+50= | | -7x-3x+2=8x-7 | | 9m+6=-6m+36 | | 3x^2+5x-5x^2-4x+5-2= | | 9y-7=11 | | 5x^4-40X^3+60x^2=0 | | -5x^2y^2= | | 5b^2-48=8b | | -64=5x-9 | | 28-4x=0 | | -20-x=-9 | | x^2+2100=92x | | (1.5-3)(V+6)= | | a^2+2a-48= | | 11m^2-11m-1=9m | | 10-8x=26 | | 3+19m-1=8m+106-2m | | 3(2-3x)+x=10(x+2)-12 | | V^2+12v-44=-7 | | 9-2y=15 | | 3x-2=5x+17 | | 9y+5y=28 | | x+x=56 | | 15y+2+2Y-1= | | 9n^2-12n-17=7 | | += | | 48x^3-147x=0 | | 3059294+929582= | | 7+(-1)/(-18)=x |

Equations solver categories